Diagnostic accuracy of malignant melanoma according to subtype. (28th November 2013) - Lin, Matthew J; Mar, Victoria; McLean, Catriona; Wolfe, Rory; Kelly, John W
Abstract Background/Objective Although there has been improvement in clinical diagnosis of pigmented superficial spreading melanomas (SSM), less common melanoma subtypes have different clinical features and may be more difficult to diagnose. The objective was to assess diagnostic accuracy for different melanoma subtypes. Methods A retrospective review was made of a random selection of SSM, nodular melanomas (NM), desmoplastic melanomas (DM) and acral lentiginous melanomas (ALM) biopsied between February 2001 and May 2012 and referred to the Victorian Melanoma Service. Clinical differential diagnoses listed on pre‐operative biopsy pathology request forms were recorded. Sensitivity for the diagnosis of melanoma was used as a marker of diagnostic accuracy. Results In total 111 SSM, 121 NM, 43 DM and 30 ALM were biopsied by 222 clinicians. Whereas diagnostic sensitivity for SSM and ALM were similar (77%, 95% CI 69–85% and 73%, 95% CI 58–89%, respectively) diagnostic sensitivity was lower for NM (41%, 95% CI 33–50%) and DM (21%, 95% CI 9–33%). Both NM and DM were diagnosed at greater tumour thickness (median 3.0 mm and 4.0 mm) than SSM and ALM (both median 1.0 mm). Amelanosis was associated with lower diagnostic sensitivity for SSM (0 vs 82%, P < 0.01), NM (19 vs 51%, P < 0.01) andDM (10 vs 32%, P = 0.07). Dermatologists were more accurate than non‐dermatologists for NM (diagnostic sensitivity 57 vs 32%, P < 0.01) and ALM (diagnostic sensitivity 94 vs 43%, P = 0.02). Conclusions Misdiagnosis of melanoma varies according to subtype and is particularly problematic for NM, DM and hypopigmented melanomas. Greater awareness of the different criteria required to diagnose these melanomas is needed.